Design and compilation of specifications for a modular‐prefabricated high‐rise steel frame structure with diagonal braces. Part I: Integral structural design. (30th August 2017) - Liu, Xuechun; Zhou, Xiaojun; Zhang, Ailin; Tian, Chen; Zhang, Xun; Tan, Yongqiang
Summary: Prefabricated steel structures have certain obvious advantages, that is, rapid construction, industrial production, and environmental protection. Although prefabricated structures have been applied in a number of countries in the world, in most cases, these structures are suitable only for low‐rise buildings, and their applications in high‐rise buildings are nota\bly rare. This paper proposes a new type of prefabricated steel structure called the modular‐prefabricated high‐rise steel frame structure with diagonal braces. Based on the T30 building, which is a hotel building with 30 storeys above the ground, the mechanical properties, failure mode, failure mechanism, and elastic–plastic development laws of the structure were studied via elastic and elastic–plastic design and analyses under various load cases and combinations. The analysis of the internal force and displacement response with frequent earthquakes was performed using the response spectrum and elastic time‐history methods, and an analysis under rare earthquakes is performed via static elastic–plastic pushover analysis. This paper summarizes the elastic and elastic–plastic structural design methods and process. This study provides important references for the design of this kind of modular‐prefabricated high‐rise steel structure, and the design method has been compiled into a design specification named Technical Specifications for Prefabricated Steel Frame Structure with Diagonal Bracing Joints .